PENGARUH PENGUNAAN SOFTWARE MAPLE 11 TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATERI DEFERENSIAL - Netriwati Netriwati (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2013)
This research aimed to find out the effect of using software maple 11 toward problem solving ability on topic of fluxion. Population on this research was the eleventh grade studend of Senior High School Bandar Sribhawono. Sample of this research is chose by using cluster random sampling technique. Data of this research gathered through test, observation and interview. Based on the research result, there was the deferenciate of the students average achievement between experiment and control class. It can be concluded that there was significant effect of using software maple 11 toward problem solving ability on topic of fluxion.